Genome-wide association study identifies a gene conferring high physiological phosphorus use efficiency in rice - Yan, Ming; Feng, Fangjun; Xu, Xiaoyan; Fan, Peiqing; Lou, Qiaojun; Chen, Liang; Zhang, Anning; Luo, Lijun; Mei, Hanwei (Frontiers in Plant Science, 2023)
Phosphate (Pi) is indispensable for the growth and development of plant, and low-Pi stress is a major limitation for crop growth and yield worldwide. The tolerance to low-Pi stress varied among rice germplasm resources. However, the mechanisms underlying the tolerance of rice to low-Pi stress, as a complex quantitative trait, are not clear. We performed a genome-wide association study (GWAS) through a diverse worldwide collection of 191 rice accessions in the field under normal-Pi and low-Pi supply in two years. Twenty and three significant association loci were identified for biomass and grain yield per plant under low-Pi supply respectively. The expression level of OsAAD as a candidate gene from a associated locus was significantly up-regulated after low-Pi stress treatment for five days and tended to return to normal levels after Pi re-supply in shoots. Suppression of OsAAD expression could improve the physiological phosphorus use efficiency (PPUE) and grain yields through affecting the expression of several genes associated with GA biosynthesis and metabolism. OsAAD would be a promising gene for increasing PPUE and grain yield in rice under normal- and low-Pi supply via genome editing.